3D printing on glass for direct sensor integration. (13th December 2019) - Neubauer, M; McGlennen, M; Thomas, S; Warnat, S
Abstract: Significant improvements are being made in 3D printed microfluidics. 3D printing of microfluidic prototypes gained importance due to the fabrication flexibility compared to conventional techniques. Applications using these devices often require optical access to internal channels but even clear resins create translucent channels due to surface roughness and imperfections. This paper describes a 3D printing approach to form fluidic channels directly onto glass substrates that allows optical access to fluidic channels without distortion from 3D printing material. The glass substrate is itself a part of the flow channel which allows optical transparency. Micro-fabricated conductivity and impedance spectroscopy sensors were fabricated on glass substrates and placed in a custom made 3D printer build plate before fluidic structures are directly printed on top of the sensors. The effects on sensor performance and properties were evaluated using co-linear four-point probe resistance measurements, Raman spectroscopy, and impedance spectroscopy. It was shown that no resin or other chemicals are left behind from the printing procedure and sensor performance was unaffected. A proof of concept impedance-conductivity sensor was integrated with a 3D printed flow channel and shown to work as both conductivity and bacterial cells detection sensor.